Factores de riesgo que desencadenan desnutrición en niños menores de 5 años en la Comunidad Awa El Guare Parroquia Chical. - Obando Chamba, Evelin Gissela (2024)
This research work was carried out with the objective of determining educational strategies that reduce risk factors that trigger malnutrition in children under 5 years of age in the Awa Guare Community, 2024. For this, various methods were needed that contributed to the development of the research, thus we have the empirical method which is scientific observation which helped to detect the existing problem in the community, creating the need to carry out the study. The methodological design used is the qualitative quantitative mixed modality paradigm, in the same way with bibliographic, field and applied research, a survey and a checklist were used as an instrument which helped to obtain direct and truthful information, previously validated. Obtaining the following most relevant results: 82% of the parents surveyed do not know what child malnutrition is, 67% of parents have an income of less than 100 dollars per month, 92% do not know the consequences of child malnutrition, 58% consider that children can be fed 2-3 times a day. This is how an action plan was designed to reduce the risk factors for malnutrition, focusing on educational strategies, education, prevention and promotion. By validating the proposal, a decrease in the risks present in this community was achieved.